2007
DOI: 10.1359/jbmr.070302
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Stimulating Hormone Restores Bone Volume, Microarchitecture, and Strength in Aged Ovariectomized Rats*

Abstract: We show the systemic administration of low levels of TSH increases bone volume and improves bone microarchitecture and strength in aged OVX rats. TSH's actions are mediated by its inhibitory effects on RANKL-induced osteoclast formation and bone resorption coupled with stimulatory effects on osteoblast differentiation and bone formation, suggesting TSH directly affects bone remodeling in vivo.Introduction: Thyroid-stimulating hormone (TSH) receptor haploinsufficient mice with normal circulating thyroid hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 34 publications
(84 reference statements)
10
112
1
2
Order By: Relevance
“…However, in vivo, in rats, TSH, injected up to once every 2 weeks, inhibits ovariectomyinduced bone loss 28 weeks following ovariectomy [73]. Calcein-labeling provides evidence for a direct anabolic action of intermittent TSH [69]. In humans, Martini et al [70] showed an increase in procollagen type I N propeptide (PINP), a marker of bone formation, validating the conclusion that bolus doses of TSH are indeed anabolic.…”
Section: Mechanism Of Actionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, in vivo, in rats, TSH, injected up to once every 2 weeks, inhibits ovariectomyinduced bone loss 28 weeks following ovariectomy [73]. Calcein-labeling provides evidence for a direct anabolic action of intermittent TSH [69]. In humans, Martini et al [70] showed an increase in procollagen type I N propeptide (PINP), a marker of bone formation, validating the conclusion that bolus doses of TSH are indeed anabolic.…”
Section: Mechanism Of Actionmentioning
confidence: 93%
“…At least 20 clinical studies have since documented tight and highly reproducible correlations between low TSH levels, bone loss, bone geometry, and fracture risk in patient cohorts across the globe . Evidence also shows that TSH protects the skeleton by exerting anti-resorptive and anabolic actions in rodent models and in people [37,[62][63][64][65][66][67][68][69][70][71].…”
Section: Thyroid Stimulating Hormonementioning
confidence: 99%
See 1 more Smart Citation
“…In the context of conflicting data on a functional role for TSH in skeletal development, our data, which were corrected for serum TSH levels, outline the importance of local T 3 for bone metabolism. (13)(14)(15)(16)(17)(35)(36)(37)(38) Two recent papers by Bassett and colleagues, (18,19) who studied mice with complete or haploinsufficiency of TRa and -b, concluded that TRa regulates both skeletal development and adult bone maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of TSH to ovariectomised rats has been shown to prevent bone loss and restore bone mass (Sampath et al, 2007;Sun et al, 2008) have demonstrated that intermittent administration of exogenous TSH in ovariectomised rats and mice have anti-resorptive effects. Recent findings indicate that TSH might play a crucial role in bone turnover in humans.…”
Section: Tsh As a Metabolic Regulatormentioning
confidence: 99%